Mindsets of craftsman:from barrier to lever - Deny Willy Junaidy; Yukari Nagai (2016)
This study discovered that Indonesian master craftsmen's conceptual process is highly influenced by Typical mindsets of Object-attribute that underlines Rationale and Mastery that thus stimulate a pragmatic perspective. We observed that traditional design education is difficult to be conceived by individuals with conservative viewpoint. Consequently, we make a model of the design training that fits with their conventional mindsets. This model utilizes traditional craftsman's previous knowledge at extraordinary levels in order for them further experiencing dialectical-beliefs of new thoughts. To further develop this model we investigate their knowledge acquisition of mindset during conceptual process